History Is in the Land : Multivocal Tribal Traditions in Arizona's San Pedro Valley - Ferguson, T. J. (Thomas John), 1950- (Book collections on Project MUSE., 2006)
"Arizona's San Pedro Valley is a natural corridor through which generations of native peoples have traveled for more than 12,000 years, and today many tribes consider it to be part of their ancestral homeland. This book explores the multiple cultural meanings, historical interpretations, and cosmological values of this region by combining archaeological and historical sources with the ethnographic perspectives of four contemporary tribes: Tohono O'odham, Hopi, Zuni, and San Carlos Apache."--Jacket